3D grain growth simulation and experimental verification in laser beam melting of IN718 - Köpf, Johannes; Rasch, Michael; Meyer, Andreas; Markl, Matthias; Schmidt, Michael; Körner, Carolin (Procedia CIRP 74 (2018), 2018)
A predictive grain structure model originally used for selective electron beam melting (SEBM) is adapted to laser beam melting (LBM). Single lines with varying welding speeds were molten in a base plate made of polycrystalline IN718. The heat input is calculated with an analytical heat source model and the resulting melt pool geometry is compared with micrographs and high-speed camera shots. A typical welding microstructure is predicted by the grain growth model and confirmed with Electron Backscatter Diffraction (EBSD) measurements. With increasing line energies, a rising fragmentation of the grains is observed. This phenomenon is explained by an analyzation of the thermal gradients at the time of solidification of the grains.<br
Keywords: laser beam melting; grain growth simulation; additive manufacturing; cellular automata

3D Grain Structure Simulation for Beam-Based Additive Manufacturing - Köpf, Johannes; Rai, Abha; Markl, Matthias; Körner, Carolin (Proceedings of the 6th International Conference on Additive Technologies iCAT 2016, 2016)

3D multilayer grain structure simulation for beam-based additive manufacturing - Köpf, Johannes; Markl, Matthias; Körner, Carolin (Simulation for Additive Manufacturing 2017, Sinam 2017, 2017)
CRIS-Team Scopus Importer:2022-06-05
Keywords: 3D; Additive manufacturing; Cellular automata; Grain structure; Multilayer; Numerical simulation

3D multi-layer grain structure simulation of powder bed fusion additive manufacturing - Köpf, Johannes; Gotterbarm, Martin; Markl, Matthias; Körner, Carolin (Acta Materialia, 2018)
In powder bed fusion (PBF) additive manufacturing, powder layers are locally melted with a laser or an electron beam to build a component. Hatching strategies and beam parameters as beam power, scan velocity and line offset significantly affect the grain structure of the manufactured part. While experiments reveal the result of specific parameter combinations, the precise impact of distinct parameters on the resulting grain structure is widely unknown. This knowledge is necessary for a reliable prediction of the microstructure and consequently the mechanical properties of the manufactured part. We introduce the adaption of a three-dimensional model for the prediction of dendritic growth for use with PBF. The heat input is calculated using an analytical solution of the transient heat conduction equation. Massively parallel processing on a high-performance cluster computer allows the computation of the grain structure on the scale of small parts within reasonable times. The model is validated by accurately reproducing experimental grain structures of Inconel 718 test specimens manufactured by selective electron beam melting. The grain selection zone within the first layers as well as the subsequent microstructure in several millimeters build height is modeled in unprecedented level of detail. This model represents the cutting-edge of grain structure simulation in PBF and enables a reliable numerical prediction of appropriate beam parameters for arbitrary applications.
Keywords: Grain structure; Numerical modeling; Crystal growth; Grain growth; Cellular automata; Additive manufacturing

Additive manufacturing of cellular structures: Multiscale simulation and optimization - Mergheim, Julia; Breuning, Christoph; Burkhardt, Christian; Hübner, Daniel; Köpf, Johannes; Herrnböck, Ludwig; Yang, Zerong; Körner, Carolin; Markl, Matthias; Steinmann, Paul; Stingl, Michael (Journal of Manufacturing Processes, 2023)
This paper introduces a multiscale and multi-purpose simulation framework to investigate selective beam melting processes for metallic cellular structures along the complete process chain, up to the topology optimization of components made of cellular materials. Process simulation methods on various length scales are introduced to analyze the relation of process strategies and resulting properties of the cellular materials, as e. g. warpage, residual stresses, material grain structure and surface roughness. Numerical homogenization methods are applied to investigate the influence of the grain structure and the topology of the cellular materials on their mechanical properties. Based on these process-dependent mechanical properties, a two-scale optimization of components made of cellular material is performed, aiming in particular on optimizing the buckling resistance of the structures. The interfaces between the different simulation tools are specified and illustrate the flexibility of the numerical framework. It is shown that consistent simulations of additive manufacturing of cellular materials - from the manufacturing process to the optimized component - provide important insights into process-structure interactions and enable tailored additive manufacturing processes.
CRIS-Team WoS Importer:2023-06-02

A Novel Approach to Predict the Process-Induced Mechanical Behavior of Additively Manufactured Materials - Kergaßner, Andreas; Köpf, Johannes; Markl, Matthias; Körner, Carolin; Mergheim, Julia; Steinmann, Paul (Journal of Materials Engineering and Performance, 2021)
The grain structure and texture of additively manufactured materials depend strongly on the local temperature gradients during the solidification of the material. These grain structures and textures influence the mechanical behavior, ranging from isotropy to transversal and orthotropic symmetry. In the present contribution, a cellular automaton is used to model the grain growth during selective electron beam melting. The resulting grain structures and textures serve as input for a mesoscopic mechanical model. The mechanical behavior on the mesoscale is modeled by means of gradient-enhanced crystal plasticity, applying the finite element method. Computational homogenization is applied to determine the resulting macroscopic elastic and plastic properties of the additively manufactured metals. A general orthotropic yield criterion is identified by means of the initial yield loci computed with mesoscopic simulations of representative volume elements. The numerical results are partly validated with experimental data.
CRIS-Team WoS Importer:2021-05-21

Automatische Optimierung der Kolbenvorlaufgeschwindigkeit beim Druckgiessen durch numerische Simulation - Hilbinger, Rolf Michael; Köpf, Johannes; Rübner, Matthias; Singer, Robert (Giesserei, 2013)

Computational optimisation of plunger movement during slow shot phase in high pressure diecasting - Hilbinger, Rolf Michael; Köpf, Johannes; Rübner, Matthias; Singer, Robert (Foundry Trade Journal International, 2012)
The influence of the plunger velocity during the slow shot phase in high pressure die casting on the filling of the casting chamber is investigated by means of modeling and cast experiments. An optimum travel speed is identified for the examined platelike casting geometry by numerical calculations. This value is determined by automatic optimisation and corresponds to a steady persisting wave at the plunger, moving with it. Casting of components and experimental verification confirm the theoretical work.

Numerical microstructure prediction by a coupled finite element cellular automaton model for selective electron beam melting - Köpf, Johannes; Soldner, Dominic; Ramsperger, Markus; Mergheim, Julia; Markl, Matthias; Körner, Carolin (Computational Materials Science, 2019)
Selective Electron Beam Melting (SEBM) refers to an additive manufacturing process of building near net shaped components layer wise by iteratively melting of metal powder using an electron beam. Due to the preheating of the material and very high scan velocities of the electron beam, the process allows large processing windows defined by different process strategies. This variety enables the adjustment of part properties by, e.g., targeting certain microstructures. However, this variety has its disadvantage in the need for costly trial and error experiments. Therefore, numerical predictions are inevitable in locating promising process parameter combinations. We present the weak coupling of a Finite-Element (FE) model with a cellular automaton (CA) model to predict the microstructure evolution during SEBM. We use an FE model for the computation of the heat input, since the temperature history mainly influences the subsequent microstructure evolution. The FE model provides precomputed temperature fields for our sophisticated CA-based crystal growth model, which successfully predicts bulk material microstructures. The compound is validated by accurately reproducing the microstructure of an additively build cylinder from CMSX-4 powder, a nickel based superalloy. Special emphasize is laid on the accurate prediction of the microstructure both in the shell as well as the core of the cylinder.
Keywords: Crystal growth; Finite element method; Additive manufacturing; Cellular automata; Nickel-base superalloy; Numerical heat solver; High performance computing; Microstructure simulation; Powder bed fusion; Selective electron beam melting

Predicting defects and material quality in castings by means of computational determination of flow length values - Hilbinger, Rolf Michael; Lohmüller, Andreas; Köpf, Johannes; Singer, Robert (International Journal of Cast Metals Research, 2011)
A new criterion for the optimisation of casting design by numerical simulation is proposed. Based on the determination of flow length values during filling in castings, possible locations of defects can be predicted together with their effect on mechanical properties. This approach is demonstrated for a magnesium casting with special emphasis on comparison with experimental results. © 2011 W. S. Maney & Son Ltd.
Keywords: Fill pattern; Filling related defects; Flow length; Numerical simulation

Topology Optimization in Additive Manufacturing Considering the Grain Structure of Inconel 718 using Numerical Homogenization - Hübner, Daniel; Gotterbarm, Martin; Kergaßner, Andreas; Köpf, Johannes; Pobel, Christoph; Markl, Matthias; Mergheim, Julia; Steinmann, Paul; Körner, Carolin; Stingl, Michael (Proceedings of 7th International Conference on Additive Technologies, 2018)
This paper introduces a new manufacturing aware design approach which exploits the possibilities of additive manufacturing processes to generate arbitrary geometries and simultaneously adjust the grain structure of the materials by choosing particular scan strategies. A combined experimental-simulative approach is developed which experimentally analyses the producible grain structures in the selective electron beam process, computes macroscopic material properties for these grain structures and employs these material properties in an optimization procedure in which the topology of a part and the orientation of the grains are optimized. In one example, the stiffness of a designed part can be increased by 30% when the grain orientation is taken into account.
Keywords: selective electron beam melting; optimization; grain structure

Vermeidung von Gussfehlern - Prognose von Eigenschaften durch Modellierung - Hilbinger, Rolf Michael; Köpf, Johannes; Lohmüller, Andreas; Scharrer, Martin; Hartmann, Mark; Singer, Robert (Druckguss, 2005)